Comparative Study of Hydroxyapatite Modified Electrode (HAp-CME) and Screen-Printed Electrode (HAp-SPE) for Pb(II) Detection - Mohd Firdaus B Rahim, Mohd Firdaus (Universiti Teknologi Petronas, 2011)
Heavy metals such as lead are among the various environmental pollutants that can be considered dangerous to the environment and living being due to high stability and ability for bioaccumulation. It is a matter of great importance to analyze and quantify in-situ these toxic agents. Methods such as atomic absorption spectrometry (AAS) or atomic emission spectrometry (AES) often require complex preparation and expensive instrumentation. Voltammetric methods by using three electrode systems particularly Square Wave Anodic Stripping Voltammetric (SWASV) has some advantages such as little or no sample pretreatment and low cost instrumentation. The aim of this project is to make the comparison study between hydroxyapatite (HAp) modified electrode (CPE) and screen-printed electrode (SPE) by using Square Wave Anodic Stripping Voltammetric (SWASV) technique for lead detection for in situ analysis.